2019
DOI: 10.3390/jcm8091466
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Offspring Long-Term Infectious Morbidity

Abstract: Obesity is a leading cause of morbidity world-wide. Maternal obesity is associated with adverse perinatal outcomes. Furthermore, Obesity has been associated with increased susceptibility to infections. The purpose of this study was to evaluate long-term pediatric infectious morbidity of children born to obese mothers. This population-based cohort analysis compared deliveries of obese (maternal pre-pregnancy BMI ≥ 30 kg/m2) and non-obese patients at a single tertiary medical center. Hospitalizations of the offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…Importantly, our findings are in agreement with previous studies in young children from other diverse backgrounds 5 , 9 , 20 . Notably, the link between maternal obesity and lower respiratory tract infections in infants under one year of age was demonstrated by Rajappan et al, who described a LRTI relative risk of 1.23 among children born to obese mothers in a longitudinal birth cohort of 2,799 British infant-mother pairs 5 .…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, our findings are in agreement with previous studies in young children from other diverse backgrounds 5 , 9 , 20 . Notably, the link between maternal obesity and lower respiratory tract infections in infants under one year of age was demonstrated by Rajappan et al, who described a LRTI relative risk of 1.23 among children born to obese mothers in a longitudinal birth cohort of 2,799 British infant-mother pairs 5 .…”
Section: Discussionsupporting
confidence: 93%
“…The findings reported in this study are of high value for midwives and obstetricians when taking care of pregnant women, and researchers, who may use them to prevent negative outcomes and enhance adequate development among infants. The perinatal period is a highly vulnerable stage when it is paramount to provide the best maternity care [60].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies associated maternal inflammatory statuses with offspring with long-term alterations of immune responses that result in childhood infectious morbidity. These maternal conditions were pure infectious diseases [ 19 , 30 , 31 ], but were also attributed to conditions such as obesity and smoking that may involve maternal subclinical inflammation [ 20 , 21 , 32 , 33 , 34 ]. This association between intrauterine inflammation and childhood morbidity, however, showed mixed trends in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies showed increased risk of short and long- term infectious morbidity in children born to mothers with an augmented inflammatory state during pregnancy. Preterm birth, maternal urinary tract infection, maternal obesity and maternal substance abuse were all demonstrated to be associated with increased infectious morbidity of the offspring [ 30 , 31 , 32 , 33 , 34 , 35 ]. We hypothesized that maternal tuberculosis can also promote an intrauterine environment that may alter immune responses of the offspring in his future.…”
Section: Discussionmentioning
confidence: 99%